2015
DOI: 10.1080/15592294.2015.1057383
|View full text |Cite
|
Sign up to set email alerts
|

Beckwith–Wiedemann syndrome prenatal diagnosis by methylation analysis in chorionic villi

Abstract: Beckwith-Wiedemann syndrome (BWS) is an imprinting disorder that can be prenatally suspected or diagnosed based on established clinical guidelines. Molecular confirmation is commonly performed on amniocytes. The possibility to use fresh (CVF) and cultured (CVC) chorionic villi has never been investigated. To verify whether CVF and CVC are reliable sources of DNA to study fetal methylation, we used pyrosequencing to test the methylation level of a number of differentially methylated regions (DMRs) at several im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Different shades of yellow indicate 5% intervals of LOM (with light yellow corresponding to slight LOM and dark yellow corresponding to heavy LOM), while different shades of blue represent 5% intervals of GOM (from light blue corresponding to slight GOM to dark blue indicating heavy GOM). The last two columns contain ICR1/ICR2 methylation values determined by pyrosequencing, according to protocols previously described [41]. *t-test ICR1 MassARRAY vs. ICR1 pyrosequencing: P  = 0.2302.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different shades of yellow indicate 5% intervals of LOM (with light yellow corresponding to slight LOM and dark yellow corresponding to heavy LOM), while different shades of blue represent 5% intervals of GOM (from light blue corresponding to slight GOM to dark blue indicating heavy GOM). The last two columns contain ICR1/ICR2 methylation values determined by pyrosequencing, according to protocols previously described [41]. *t-test ICR1 MassARRAY vs. ICR1 pyrosequencing: P  = 0.2302.…”
Section: Resultsmentioning
confidence: 99%
“…All cases included in the study had a primary methylation defects at ICR1/ICR2, as confirmed by molecular diagnosis by pyrosequencing [4143]. Genomic imbalances or UPD were excluded by SNP array (Supplementary materials and methods).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that some DMRs are not finally established during the time of CVS in the 10-12th wp, 44 and methylation-specific testing at that time leads to false results, explaining the false-positive case in our cohort (Tables 3a and b). Mosaicism can cause a false-negative testing result as shown in our study cohort (Tables 3a-c).…”
Section: Challenges For Prenatal Testing In Bws and Srsmentioning
confidence: 87%
“…Furthermore, in the case of early CVS (before 12 wp) the imprinting marks at the loci of interest might not be finally set. 44 As CVS is an extraembryonic tissue, it might not reflect the (epi)genetic constitution of the fetus. Although the analysis of cells derived from the fetus itself offers the best chance to detect altered imprinting marks, our data show that even in this case the risk of false-positive results cannot be prevented (Table 3b).…”
Section: Prenatal Tissuementioning
confidence: 99%
“…An accurate molecular prenatal diagnosis is often challenged by heterogeneity and frequent mosaicism of the genetic/epigenetic alterations [7]. In addition, the offered tests must take into account the source of fetal cells, because methylation patterns of embryonic and extraembryonic tissues may differ from those of adult tissues [165,166]. For these reasons, prior to offering prenatal diagnosis based on methylation testing, a detailed presentation of the technological limitations should be discussed with the parents; in particular, they should be made aware that a normal result does not necessarily exclude the suspected diagnosis.…”
Section: Dna Methylation Analysis In Prenatal Diagnosismentioning
confidence: 99%